1974
DOI: 10.1042/cs0460019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin on Plasma Electrolyte Concentrations in Rabbits and in Man

Abstract: 1. The effects of an intravenous infusion of angiotensin on plasma electrolytes were examined in normal, adrenalectomized and nephrectomized groups of rabbits and in normal man. Rabbits were given 1 pg kg-I min-' and human subjects 0.008-0.030 pg kg-' min-' of angiotensin.2. In normal rabbits, angiotensin increased arterial and venous plasma K within 2 min by 0.8 and 0.4 mmol I-' respectively, some hyperkalaemia persisting for 30-60 min. After 60 rnin arterial plasma Na decreased by 3.8 mmol I-' and C1 by 2.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
2
2
0
Order By: Relevance
“…Captopril, through its effect on eliminating angiotensin II formation, may have retarded the expected rise in plasma potassium concentration after potassium infusion. This is consistent with the demonstration by Healy et al (34) that angiotensin II administered to the rabbit and to humans causes plasma potassium levels to increase. An effect of captopril to curtail potassium as a stimulus by preventing potassium levels to increase sufficiently was considered in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Captopril, through its effect on eliminating angiotensin II formation, may have retarded the expected rise in plasma potassium concentration after potassium infusion. This is consistent with the demonstration by Healy et al (34) that angiotensin II administered to the rabbit and to humans causes plasma potassium levels to increase. An effect of captopril to curtail potassium as a stimulus by preventing potassium levels to increase sufficiently was considered in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…and g.f.r., the mechanism responsible for the natriuresis remains unclear. The possibility of a direct action of angiotensin on proximal tubular sodium reabsorption has been shown previously (Harris & Young, 1977) and is supported by the study of Healy & Elliott (1971) who showed that angiotensin-induced natriuresis in rabbits occurs even when the increase in blood pressure is prevented by haemorrhage.…”
Section: Cb24atsupporting
confidence: 61%
“…A similar view has been expressed by Healy et al (1974), who first demonstrated this important action of the octapeptide, in conscious rabbits.…”
Section: Control Datamentioning
confidence: 61%
“…Except for the dose-response studies, the dose of angiotensin I or II was given on a weight-related basis, where W was the weight of the sheep in kilograms, and the concentration (pg/ml) ofthe decapeptide was 5/8 H^and that of the octapeptide 1/2 W. The concentrations achieved in unit time were approximately equimolar in individual sheep and similar to those reported previously (see Healy, Elliott & Harrison, 1974;. In contrast, the dose of catecholamines was not related to the weight of the animal.…”
Section: Infusion Of Peptides and Catecholaminesmentioning
confidence: 82%